Wegener’s granulomatosis masquerading as Pansinusitis and Nasal Polyposis: a diagnostic Dilemma - Giri, Apoorv; Bakshi, Arun P; Umap, Pradeep S; Shrikhande, Anuradha V (Indian Journal of Case Reports, 2017)
Wegener’s Granulomatosis is characterized by granulomas of the upper and lower respiratory tracts, glomerulonephritis and systemic vasculitis of small and medium sized vessels. A “limited” form of the disease points to the presence of clinical findings restricted to the upper respiratory tract and/or lungs. Limited sino-nasal disease is rare and, coupled with the higher incidence of tuberculosis, bacterial and fungal sinusitis, a timely diagnosis often poses a challenge. We present a case of a female patient in the seventh decade with features of pansinusitis and nasal polyps, initially diagnosed as, granulomatous lesion of infective etiology, which later turned out to be Wegener’s granulomatosis.